Optimized New Efficient Load Balancing Technique For Scheduling Virtual Machine - Preethi, B.; Kamalanathan, Prof. C. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Cloud computing offers advantage in cost, scalability, flexibility to its users. Load balancing is essential for optimization of resources in distributed environments. The major goal of the cloud computing service providers is to use cloud computing resources efficiently to enhance the overall performance in all aspects. Cloud load balancing simply distributes workload across multiple servers or data centers, network links, central processing units, disk drives, on the cloud, i.e. within the Internet itself. This method, as other load balancing methods, helps to achieve optimal resource utilization, maximize throughput, minimize response time, and avoid overload of resources. The performance of the algorithm is analyzed using Cloudsim simulator and cloud analyst .The simulation result ensures that all the processors in the system as well as in the network does approximately equal amount of work at any instant of time by comparing with other algorithms by its spoofing abilities and paving way for green computing.